Itching as the onset of pain (part 3) - Kushnir, Valerii; Dmytrenko, Svitlana; Katilov, Oleksandr; Kushnir, Natalia (Pain medicine, 2020)
Itchy skin is an extremely unpleasant symptom that can provoke insomnia, depression, irritability, loss of appetite. There are several theories of itching. According to one of them, itching is a modified pain caused by a slight irritation of the nerve endings in the skin. According to the second, itching is an independent symptom, in the formation of which nervous, humoral and vascular mechanisms are involved. Other theories consider itching as a reaction of the autonomic nervous system or a hereditary pathological condition. According to recent studies, itchy skin is characterized by the absence of a universal peripheral mediator of itching. The trigger for itching is the action of pruritogen – a mechanical, chemical, thermal or electrical stimulant directly or indirectly through mediators. Free ends of type A delta fibers and type C fibers play a crucial role in itching and pain. If this was previously confirmed only by clinical observations, now there are neurophysiological studies that support the theory that itching and pain fibers are one with different activity thresholds. Today, it is unacceptable that there are separate specific receptors for different sensations. It is now assumed that there are mixed receptors for heat, cold, pain, itching and touch [95]. Systematic use of substances included in the list of drugs and manifested by mental and physical dependence on them – drug addiction, one of the diseases of society. But drug addiction is sometimes forced, according to medical indications, in cases of palliative conditions. Depending on the stage of the person after taking the drug or in the interval between drug use, one of the signs of use may be severe itching of the skin. And after excluding both the main diseases that cause itching and other secondary causes of itching, it can be assumed that a person has idiopathic generalized pruritus (itching) of unknown origin (GPOU). The itching of the elderly, which is quite common in the elderly, as a manifestation of concomitant, often combined, somatic pathology, but may also be due to physiological changes, both on the skin and on the physiological aging of nerve endings.